Augmented Reality in Retail Transforming Shopping Experiences through Interactive Product Visualization - Chinthamu Narender; Balaram Allam; K Sowjanya Bharathi; S Saravanan; J S Jaslin; T Saravanan (ITM Web of Conferences)
Extend Reality (AR) is changing the retail industry, offering immersive and interactive product visualization experiences. This paper differs from past literature as it is the first to focus on AR in retail from a numerical and quantitative perspective, with a framework that is based on real samples in the industry that may close the gap between theory and practice. Drawing on an extensive academic literature review and case studies from diverse retail domains such as fashion, electronics and grocery shopping, this study dissects the impact of AR on user experience, customer engagement and purchasing behaviour. It also explores the technological, psychological and security impediments to AR adoption and offers strategic insights into scalable implementation. Utilizing AR, the study illustrates optimisation of marketing strategies, favourable consumer trust and ultimately long-term consumer retention in mustering artificial intelligence, data analysis and personalisation methods. In addition, the study examines the role of AR in sustainable retailing, business model formation, and future trends like blockchain-based AR transactions and 5G-enhanced experiences. By comparing AR with conventional retailing and other emerging digital shopping technologies, the present study demonstrates the disruptive capability of AR in revolutionizing the future of shopping experience.